SYMPTOMATIC VALLECULAR CYST- HOW I DO IT? - DR.S.SUNDARA PANDIAN; DR.ABERNA GOVARTHANARAJ (International Journal of Pharma and Bio Sciences, 2014)
Vallecular Cysts are usually retention cysts of the minor salivary glands. They arise due to blockage of mucous gland duct. Other names for vallecular cyst are mucus retention cyst, pre –epiglottic cyst, base of the tongue cyst and the ductal cyst .Congenital cysts of the larynx are rare, presenting either in infancy or in adults. Small vallecular cysts are asymptomatic; as it gets bigger due to mucous accumulation it may cause stridor or difficulty in swallowing. Common site of occurrence is lingual surface of epiglottis. Here we report a case of adult vallecular cyst presented with complaints of change in voice, slight discomfort while swallowing and breathing which was treated surgically in a unique way by using an endoscope and micro debrider .The conventional modalities of management of vallecula cyst include marsupialisation, de-roofing or excision or electrocautery.